Acoustic properties of gas bubbles coated with monolayers of oil substance - Stanisław J. POGORZELSKI; Khalifa S. SAEID (Archives of Acoustics, 2015)
A gas bubble coated with a monolayer of oil substance, submerged in liquid, in the field of an acoustic wave is given theoretical consideration in this paper. Radial oscillations in the wave frequency band much below the resonance frequency depend mainly on the value of the monolayers modulus of elasticity and relaxation time t_r of the process of molecule reorientation which occurs in the monolayer due to its deformation. The following parameters were calculated: shift of the resonance frequency, damping constant of radial oscillations, and acoustic wave scattering and extinction cross-sections for a gas bubble in water, coated with a condensed monolayer of Extra 15 engine oil in angular frequency range ω ∈ [10^1 ÷ 10^5] rads^{-1} and range of radii of bubbles (3-50) μm. Predicted values of the damping constant and extinction cross-section in the wave frequency range ω < α(α = 2π/t_r) are by several orders of magnitude greater than those for a bubble with a clean srface. This effect is especially distinct in the case of microbubbles (with μm radii and smaller) placed at small depths (up to about 0.5 m).